Propuesta curricular de habilidades adaptativas para la estimulación temprana de niños y niñas de 0 a 3 años de edad, con discapacidad cognitiva - Jara Ocampo, María Guillermina; Roda Fuentes, Pahola (Revista Electrónica Educare, 2010)
Abstract. The study developed builds a curriculum proposal based on adaptive skills for early stimulation of children from 0 to 3 years with cognitive disabilities as a final requirement for graduation from the Masters in Education with Emphasis on Development The proposal intends to improve the coherence, relevance and effectiveness of special education offered to students with special educational needs, specifically with cognitive impairment conditions, from early stimulation with a population of 0 to 3 years. The main objective of the study rises from the working context of the study: the individual needs of special education teachers and their students.